Impact of bacteroides uniformis on fatty liver hemorrhagic syndrome in dawu golden phoenix laying hens: modulation of gut microbiota and arachidonic acid metabolism - Zhang, Yu; Ma, Rongfei; Du, Xicui; He, Xin; Zhang, Yan; Ma, Ning; Liu, Hailong; Zhao, Xinghua (Frontiers in Microbiology, 2025)
This study explored the impact of Bacteroides uniformis (B. uniformis) on fatty liver hemorrhagic syndrome (FLHS) induced by a high-energy and low-protein (HELP) diet in laying hens, mainly focusing on hepatic lipid metabolism, gut microbiota, and arachidonic acid (AA) metabolism. A total of 120 Dawu Golden Phoenix laying hens (210-day-old) were randomly divided into four groups. The control group (CON) was fed a standard diet and received a daily gavage of PBS, while the other groups were fed with a HELP diet to induce FLHS and received a daily gavage of PBS (MOD), 1 × 109 CFU/ml B. uniformis (BUL), and 1 × 1011 CFU/ml B. uniformis (BUH) for 70 days. All hens were administered 1 ml daily by gavage. Each group had 6 replications with 5 hens per replication. The results showed that B. uniformis increased the egg production rate and feed conversion ratio and decreased body weight, liver index, and abdominal fat rate (p < 0.05). B. uniformis treatment reduced liver lipid accumulation by reducing the levels of Triglyceride (TG), Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), alanine transaminases (ALT), and aspartate transaminases (AST) in serum and significantly elevated high-density lipoprotein cholesterol (HDL-C) (p < 0.05). The results indicated that B. uniformis altered the gut microbiota. Specifically, the abundance of Bacteroides was higher, and the relative abundances of Treponema, Helicobacter, and Spirochaetota were lower than those of the MOD group (p < 0.05). Moreover, targeted metabolomic analysis showed that supplementation of B. uniformis significantly elevated 6-keto-PGF1α and AA levels, along with significantly reduced levels of thromboxane B2 (TXB2), leukotriene D4 (LTD4), 8-isoprostaglandin F2α (8-iso-PGF2α), 12S-hydroxyeicosatetraenoic acid (12S-HETE), 15S-hydroxyeicosatetraenoic acid (15S-HETE), 9-S-hydroxy-octadecadienoic acid (9S-HODE), and 13-S-hydroxy-octadecadienoic acid (13S-HODE) (p < 0.05). In conclusion, the oral intake of B. uniformis can improve liver function, gut microbiota, and AA metabolism, thereby helping to ameliorate FLHS in Dawu Golden Phoenix laying hens.